PENINGKATAN KETERAMPILAN GENERIK SAINS BAGI MAHASISWA MELALUI PERKULIAHAN PRAKTIKUM KIMIA ANALISIS INSTRUMEN BERBASIS INKUIRI (Universitas Negeri Semarang, 2008)
This research was aimed to improve the generic skill (observation, sense of scale,causality, logical frame, and logical inference) of students. The research was conductedby using education research and development design. The data were collected by test,questionnaire, and observation sheets. The subject of research was fourth semester studentsof chemistry education programme of educational institute of Central Java. Achievement ofgeneric skill enhancement was evaluated by written exam, deed test, work observation, andstudents’ work results. The result of research showed the signifi cant enhancement of thewhole developed aspects. The success was shown also by the students’ positive attituderesponse.Keywords: science generic skill; instrument analytical chemistry